STATE-OWNED COMPANY BOARD DIVERSITY: DRIVING OR DRAINING FINANCIAL PERFORMANCE? - Anthony Holly; Ana Mardiana; Robert Jao; Fransiskus Randa (AJAR, 2026)
This study aims to examine the impact of board of directors' characteristics—specifically gender diversity (proportion of female directors), board size, and director age—on financial performance. Grounded in agency theory and resource dependency theory, this quantitative research utilizes secondary data collected through documentation from the annual reports of State-Owned Enterprises (SOEs) covering the 2022–2024 period. Using a purposive sampling technique, the study reveals that board characteristics, namely the proportion of women, board size, and average age, exert a significant negative effect on financial performance.